(untitled) (Research, Society and Development, 2021)
This study analyzed the main characteristics of two universal systems, the National Health Service (NHS), in the United Kingdom, and the Unified Health System (SUS), in Brazil, in relation to oral health care actions and services. A literature review, document and secondary data analysis were performed from official databases in Brazil and the United Kingdom. There were differences in financing, covered population, infrastructure, organization, provision and management of actions and services. The sociodemographic and oral health indicators are more unfavorable in the Brazilian situation, however, inequalities persist also in the United Kingdom. In both countries, health is seen as a constitutional right, but NHS oral health actions are restricted to a specific public and offered by professionals from the private sector, with a large part of the cost of procedures by families. Successive reforms of the NHS have contributed to restricting access. The SUS, on the other hand, presents oral health services, primary and specialized care, universal and public offer, even if the coverage is insufficient and with problems in implementation. Austerity measures have been identified as a threat to the principles of universality and integrality in both countries. Comparative analysis helps in the identification of elements that contribute to the advancement of public provision of dental care.